Implementing Physical Education via UNNES Lantip - Reza Rachman; Agung Wahyudi Wahyudi; Ricko Irawan Ricko (Universitas Negeri Semarang, 2026)
The UNNES Lantip Program is one of the implementations of the Merdeka Belajar Kampus Merdeka (MBKM) initiative, aimed at providing teaching experience for university students while supporting schools in the learning process. This study aims to describe the implementation of Physical Education, Sports, and Health (PE) learning through the 2nd Batch of the UNNES Lantip Program at SDN Wonosari 03 Semarang. The study employed a qualitative descriptive method, utilizing observation, documentation, and direct teaching practice at the school as data collection techniques. The program was conducted from July 12 to September 30, 2022, at SDN Wonosari 03 Semarang. The activities included school observation, supervised teaching practice, independent teaching practice, preparation of instructional materials and lesson plans, and learning evaluation. The results indicate that the program successfully enhanced the teaching experience of university students, assisted teachers in the implementation of PElearning, and increased student participation through the use of diverse instructional media and teaching methods. Supporting factors included the guidance provided by mentor teachers, the availability of school facilities, and the cooperation of students. Meanwhile, the challenges encountered involved classroom management, the limited teaching experience of student participants, and communication that was not yet fully optimal.